Ciência do sagrado na Amazônia. Encontros entre a tradição e modernidade nas práticas de pajelanças e religiões afro-brasileiras - NASCIMENTO, Ana Lídia Cardoso do (Universidade Federal do Pará, 2018)
The cure process by means of empiric knowledge of experience and livingness always been part of social and cultural relation of human population in different context of realities. And the amazon reality as beares of richness and potentiality of sociobiodiversity sustain with natural crativity of religious beliefs framework mistical and magical character. The same, will give opportunity the construction of a scape based on ancestral heritage with the indigenous pajelança interspected of new settings about creative power from natives of Amazon of pajelança and their syncretic and sinthetyc nature of many other influences and the insertion of african religiosity even not being originating of amazon, understand with intelligence and wisdom the knowledge already existent and resignify their religiosity. In this sense, the discution as these, in their procedures and rituals , may generate instituting body that was stipulated to call in the present work as sacred science. In this drawing that this research was constructed in the sense to identify a construction of a scienceas sacred, guided by the light and direction of this religious practices. That not only represents and are identified as religion, but also expand horizon and expand their comprehension of world and religion to relate and be mediator of spiritual entities with supernatural knowledge that are in different dimension of rationa science. The intention of this study was to reach various geographical areas in the same time similar in the construction of perception and religious practices in the paraense Amazon and extrapoling the limits up to enter in the Pan-Amazonia on Triple Frontier: Brazil, Colombia and Peru. Thus, the search field was in the state of Pará, was worked with the metropolitan region of Belém, cities as: Belém, Ananindeua and Marituba; In the Marajó archipelago: Juruti city. And the Triplice Frontier the cities of Tabatinga-Ma and Letícia-Co. The basic theoretical categories were: sacred and religiosity and science on Amazon, indigenous sacred, afrobrazilian religion, pajelança founded to the discution of ―South Espistemology‖, ―perspectivism ameridian or indigenous‖. The methodology adopted has an interdisciplinary orientation, guided by qualitative and documental research , understanding the reality in the multidimensional nature. And, in function of these theoretical discution associated with analysis of knowledge and productions of people autonomus of cure , it is concluded that exist an instituted science, with a body of knowledge , principles methodologies and appopriate techniques were exist people that are benefited and with effective support that the application of such knowledge can bring improvement of live and changes the state of embalance installed.